Skills in clinical communication: Are we correctly assessing them at undergraduate level? - Alberto Zamora Cervantes; Carme Carrión Ribas; Ferran Cordón Granados; Bibiana Galí Pla; Elisabet Balló Peña; Miquel Quesada Sabate; Armand Grau Martin; Antoni Castro Guardiola; Silvia Torrent Goñi; Susanna Vargas Vila; Esther Vilert Garrofa; Enric Subirats Bayego; et al. (OmniaScience, 2014)
Communicating with the patient in clinical practice refers to the way in which the doctor and the patient interact both verbally and nonverbally, in order to achieve a shared understanding of problems and solutions. Traditional learning and assessment systems are overwhelmed when it comes to addressing the complex and multi-dimensional problems of professional practice. Problem Based Learning (PBL) has been put forward as an alternative to the mere reproduction of knowledge and pre-established patterns, enabling students to develop their own learning strategies to overcome problems in their future professional practice. The challenge is to determine how to assess the acquisition of clinical communication skills. The authors have recommended a summative assessment of clinical communication skills based on the combination of different methods. It highlights the importance of feedback-based formative assessment. This raises the need to develop and validate assessment scales in clinical communication at an undergraduate level. Based on this work, the authors put forward a "fanned out" assessment in terms of clinical communication skills in Medicine degrees, with the use of different instruments in a "spiraled" manner, where the greater the contact with clinical practice in the various degree and integral courses, the greater difficulty experienced, with the participation of all the stakeholders involved (self, hetero and peer assessment) without precluding the involvement of patients (real or simulated) in the design of assessment instruments.